Kontribusi Kemampuan Manajerial Kepala Madrasah, Sarana Prasarana, Dan Budaya Kerja Terhadap Kinerja Guru Madrasah Aliyah Di Kabupaten Wonogiri - Warno, Warno, Dr. Suyatmini, MSi, Drs. Budi Sutrisno, M.Pd (2015)
The purpose of this research is to find empirical evidence on the contribution of managerial ability headmaster , means infrastructures , and work culture with the performance of Madrasah Aliyah in Wonogiri. This type of research uses a form of quantitative research and the use of random sampling research design. The population of this research is Professor Madrasah Aliyah in Wonogiri Ministry of Religious Affairs Wonogiri . Number of Teachers Madrasah Aliyah in Wonogiri is 132 people . By taking a sample of 125 teachers randomly selected as respondents. The results showed that there is a positive kontrtibusi between variables headmaster managerial capabilities , infrastructure , and culture on the performance of Madrasah teachers in Wonogiri . Contribution managerial ability headmaster on teacher performance Madrasah Aliyah at 2,016 , variable contribution of infrastructure to the madrassa teacher performance by 4,019 , and the contribution of the variables on the performance of teachers' work culture at Madrasah Aliyah 6,579 , while the contribution of managerial ability headmaster , infrastructure , and work culture on teacher performance Madrasah Aliyah by 0,622 or 62,2 %. From these results it is suggested that the staffs are continuously trying to improve managerial skills , develop infrastructure , and creating a work culture that is conducive for Madrasah Aliyah teacher performance can be achieved with a good lead. Key words: culture, infrastructure, madarasah, managerial, performance